PARTISIPASI POLITIK ETNIS TIONGHOA DALAM KEIKUTSERTAAN PEMILUKADA DI KABUPATEN KUANTAN SINGINGI TAHUN 2015 - Rosita "; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In 2015 Rokan Hulu has confirmed the Draft Budget Revenue and Expenditure (budgets) Rokan Hulu in 2015 to (Perda) Government Budget Rokan Hulu in 2015 with a total of Rp. 1,566 trillion. The budget deficit of Rp. 273 billion due to the reduction in Fund Balance of the Central Government. In contrast to the passage of budgets in 2015, apparently in the process of preparation of the proposed budget amendment of 2015 is not like a trip to the discussion of budgets approved in 2015. The adjustment of the budget with the development and changes in circumstances should be discussed with the Provincial Government and Rokan Hulu in the framework of the preparation of forecasts of changes in the budget financial year 2015 to be no impact. However, up until 31 December 2015 RAPBD-P 2015 are not being discussed.The study was made by using Qualitative Approach (Qualitative Approach) with qualitative analysis model. This study attempted to look at the phenomenon that is on the field and then analyzed by comparing the various theories that have been presented so clearly visible gaps between das sollen and das sein. Based on the findings of this study show that: First, political communication between the local government (Local Government) and Parliament (DPRD) Rokan Hulu runs less harmonious, this is evidenced by vulnerable time between the letter as a medium of political communication is very long and too late in terms of the rule of law in the discussion RAPBD-P Year 2015. second, technical factors (normative) and political factors that affect political communication between the two institutions in the discussion RAPBD-P 2015.Keywords: Political Communication, Local Government, Parliament, RAPBD-P.